2013
DOI: 10.1371/journal.pone.0054996
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Rock the Boat: How Antiphase Crew Coordination Affects Rowing

Abstract: It is generally accepted that crew rowing requires perfect synchronization between the movements of the rowers. However, a long-standing and somewhat counterintuitive idea is that out-of-phase crew rowing might have benefits over in-phase (i.e., synchronous) rowing. In synchronous rowing, 5 to 6% of the power produced by the rower(s) is lost to velocity fluctuations of the shell within each rowing cycle. Theoretically, a possible way for crews to increase average boat velocity is to reduce these fluctuations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 30 publications
6
47
1
Order By: Relevance
“…They could provide further understanding of gaze behaviors exhibited by people during interpersonal performances such as in dance, musical or sport activities (de Brouwer, de Poel, & Hofmijster, 2013; Kawase, 2014; Phillips-Silver & Keller, 2012; Sevdalis & Keller, 2011; Travassos, Araújo, Vilar, & McGarry, 2011). They could also be of particular interest in the understanding of interpersonal coordination during everyday social interactions, and in particular, the disorders occurring with certain mental illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…They could provide further understanding of gaze behaviors exhibited by people during interpersonal performances such as in dance, musical or sport activities (de Brouwer, de Poel, & Hofmijster, 2013; Kawase, 2014; Phillips-Silver & Keller, 2012; Sevdalis & Keller, 2011; Travassos, Araújo, Vilar, & McGarry, 2011). They could also be of particular interest in the understanding of interpersonal coordination during everyday social interactions, and in particular, the disorders occurring with certain mental illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this rationale, Halbesleben, Novicevic, Harvey, and Buckley (2003) concluded that temporal complexity (the ability to understand time frames, tempo, synchronization, and sequence) is a competence that takes time to develop. Similarly, teams such as rowing crews (e.g., De Brouwer, De Poel, & Hofmijster, 2013), orchestras (e.g., Barrett, 1998), and professional sports teams (e.g., Rogers, 2009;Sando, 2008) report that getting into the "in sync" zone of coordination evolves over time. Therefore, the positive effect of temporal TMMs on team outcomes may become more pronounced later in a team's life cycle.…”
Section: Temporal Tmms Over Timementioning
confidence: 99%
“…The variability of relative phase serves as an indicator of the consistency of crew coordination. 12,14,15 A small amount of variation in relative phase indicates a more stable coordination, which is more resilient to perturbations, 16,17 such as due to internal (eg, temporary loss of attention) or external (eg, turbulent water conditions) sources of noise.…”
Section: Coordination Dynamicsmentioning
confidence: 99%
“…In particular, at lower stroke rates, the stroke cycle deviates from perfect harmonicity. 14,15 Therefore, we also determined a discrete measure of relative phase based on point estimates of oar angle extrema near the catch and finish of the stroke, which was calculated for each full cycle as follows:…”
Section: Relative Phasementioning
confidence: 99%